Pengaruh Dukungan Organisasional yang Dipersepsikan terhadap Komitmen Organisasional dengan Kepuasan Kerja sebagai Mediasi: (Studi pada Karyawan Desa Swan Villas & Spa, Keramas) - Ni Luh Putu Sinta; Ida Bagus Ketut Surya (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study aims to analyze the effect of perceived organizational support on organizational commitment, with work satisfaction serving as a mediating variable. The research was conducted at Desa Swan Villas & Spa, Keramas, Gianyar, Bali, involving 62 employees selected using a non-probability sampling method with a saturated sampling technique. Primary data were collected through structured questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The analysis examined both the direct and indirect relationships among the variables. The findings indicate that perceived organizational support has a positive and significant effect on organizational commitment, demonstrating that employees who perceive stronger organizational support tend to develop higher commitment toward the organization. In addition, work satisfaction has a positive and significant effect on organizational commitment, suggesting that satisfied employees are more likely to remain loyal and dedicated to organizational goals. The results also show that perceived organizational support positively and significantly influences work satisfaction, indicating that supportive organizational practices contribute to higher employee satisfaction. Furthermore, work satisfaction partially and complementarily mediates the relationship between perceived organizational support and organizational commitment, meaning that organizational support enhances commitment both directly and indirectly through increased job satisfaction. The study concludes that strengthening organizational support and improving employee satisfaction are essential strategies for fostering stronger organizational commitment and maintaining sustainable organizational performance.